Inverse Psoriasis: From Diagnosis to Current Treatment Options - Micali G; Verzì AE; Giuffrida G; Panebianco E; Musumeci ML; Lacarrubba F (Dove Medical Press, 2020)
Giuseppe Micali, Anna Elisa Verzì, Giorgia Giuffrida, Enrico Panebianco, Maria Letizia Musumeci, Francesco Lacarrubba Dermatology Clinic, University of Catania, Catania, ItalyCorrespondence: Giuseppe MicaliDermatology Clinic, University of Catania, Via S. Sofia 78, Catania 95123, ItalyTel + 39 095 321705Fax + 39 095 3782425Email cldermct@gmail.comAbstract: Inverse psoriasis represents a clinical variant of psoriasis that is sometimes difficult to diagnose due to its clinical similarity with other skin disorders involving the folds, mainly including mechanical intertrigo, fungal and bacterial infections, contact dermatitis, seborrheic dermatitis, and lichen planus. Dermoscopy represents a useful tool for an enhanced non-invasive diagnosis. The treatment of inverse psoriasis may be challenging and include topical corticosteroids, topical calcineurin inhibitors, vitamin D analogs, traditional oral systemic therapies such as cyclosporine and methotrexate, and biologic therapies.Keywords: psoriasis, inverse, diagnosis, dermoscopy, confocal microscopy, treatment